Assessing the discordance rate between local and central HER2 testing in women with locally determined HER2‐negative breast cancer. Issue 17 (13th June 2014) - Kaufman, Peter A.; Bloom, Kenneth J.; Burris, Howard; Gralow, Julie R.; Mayer, Musa; Pegram, Mark; Rugo, Hope S.; Swain, Sandra M.; Yardley, Denise A.; Chau, Miu; Lalla, Deepa; Yoo, Bongin; et al.
Abstract : BACKGROUND: The importance of human epidermal growth factor receptor 2 (HER2) as a prognostic and predictive marker in invasive breast cancer is well established. Accurate assessment of HER2 status is essential to determine optimal treatment options. METHODS: Breast cancer tumor tissue samples from the VIRGO observational cohort tissue substudy that were locally HER2‐negative were retested centrally with both US Food and Drug Administration (FDA)‐approved immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) assays, using FDA‐approved assay cutoffs; results were compared. RESULTS: Of the 552 unique patient samples centrally retested with local HER2‐negative results recorded, tumor samples from 22 (4.0%) patients were determined to be HER2‐positive (95% confidence interval [CI] = 2.5%‐5.7%). Of these, 18 had been tested locally by only one testing methodology; 15 of 18 were HER2‐positive after the central retesting, based on the testing methodology not performed locally. Compared with the 530 patients with centrally confirmed HER2‐negative tumors, the 22 patients with centrally determined HER2‐positive tumors were younger (median age 56.5 versus 60.0 years) and more likely to have ER/PR‐negative tumors (27.3% versus 22.3%). These patients also had shorter median progression‐free survival (6.4 months [95% CI = 3.8‐15.9 months] versus 9.1 months [95% CI = 8.3‐10.3 months]) and overall survival (25.9 months [95% CI = 13.8‐not estimable] versus 27.9 months [95% CI = 25.0‐32.9 months]). CONCLUSIONS: This study highlights the limitations of employing just one HER2 testing methodology in current clinical practice. It identifies a cohort of patients who did not receive potentially efficacious therapy because their tumor HER2‐positivity was not determined by the test initially used. Because of inherent limitations in testing methodologies, it is inadvisable to rely on a single test to rule out potential benefit from HER2‐targeted therapy. Cancer 2014;120:2657–2664. © 2014 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Abstract : Breast tumor samples from patients in the VIRGO observational cohort study originally determined to be negative for HER2 (human epidermal growth factor receptor 2) were retested using both immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) (n = 552); of these, 22 (4%) were found to be HER2‐positive. Eighteen samples were initially assessed with a single test, and 15 of these were determined to be HER2‐positive with the testing methodology (IHC or FISH) not performed initially. These results highlight the value of using multiple tests to assess HER2 status to ensure patients do not forgo potentially efficacious therapy.